Evaluating climate-related financial policies’ impact on decarbonization with machine learning methods - Paola D’Orazio; Anh-Duy Pham (Scientific Reports)
Abstract This study examines how Climate-Related Financial Policies (CRFPs) support decarbonization and renewable energy transitions across 87 countries from 2000 to 2023. Using the Policy Sequencing Score (PSS) and a bindingness-weighted adoption indicator, it explores the relationships between CRFPs, CO2 emissions, and Renewable Energy Production (REP) across diverse economic and institutional contexts. Findings reveal significant variation in outcomes. Advanced economies and OECD countries leverage structured policies and robust institutions to achieve steady emissions reductions and REP growth, with diminishing returns at higher policy intensities. Emerging Markets and Developing Economies (EMDEs) face institutional and structural constraints but show strong responsiveness to targeted policies, particularly in Sub-Saharan Africa and South Asia, where renewable energy growth potential is notable. Regions such as Latin America and East Asia display mixed trends, reflecting unique challenges and opportunities. Binding policies prove essential for environmental outcomes, particularly in institutionalized settings, while EMDEs require capacity building and international cooperation to address barriers. This study highlights the importance of tailoring CRFPs to specific contexts, emphasizing policy sequencing, enforcement, and capacity building. By identifying global and regional variations, the findings provide actionable insights for aligning financial systems with climate goals, fostering a sustainable low-carbon transition, and addressing equity challenges.